2017
DOI: 10.1007/s00204-017-2090-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiple microRNAs function as self-protective modules in acetaminophen-induced hepatotoxicity in humans

Abstract: Acetaminophen (APAP) overdose is the leading cause of acute liver failure. Yet the mechanisms underlying adaptive tolerance toward APAP-induced liver injury are not fully understood. To better understand molecular mechanisms contributing to adaptive tolerance to APAP is an underpinning foundation for APAP-related precision medicine. In the current study, the mRNA and microRNA (miRNA) expression profiles derived from next generation sequencing data for APAP-treated (5 and 10 mM) Hep-aRG cells and controls were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…Additionally, miR-149-3p inhibits the proliferation, migration, and invasion of bladder cancer cells by targeting the S100A4 protein, which is involved with cellular differentiation, motility, and regulating transcription [ 46 ]. Upregulation of miR-224-5p has been found to occur as part of the protective adaptive response of hepatocytes during acetaminophen-induced toxicity, and this upregulation of miR-224-5p was associated with suppression of drug metabolizing enzyme levels [ 47 ]. Using a streptozotocin-induced diabetic rat model, Mohan et al demonstrated the utility of urinary exosomal miR-451-5p as an early biomarker of diabetes-associated nephropathy, and the elevated levels of miR-451-5p appeared to be protective against kidney fibrosis [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, miR-149-3p inhibits the proliferation, migration, and invasion of bladder cancer cells by targeting the S100A4 protein, which is involved with cellular differentiation, motility, and regulating transcription [ 46 ]. Upregulation of miR-224-5p has been found to occur as part of the protective adaptive response of hepatocytes during acetaminophen-induced toxicity, and this upregulation of miR-224-5p was associated with suppression of drug metabolizing enzyme levels [ 47 ]. Using a streptozotocin-induced diabetic rat model, Mohan et al demonstrated the utility of urinary exosomal miR-451-5p as an early biomarker of diabetes-associated nephropathy, and the elevated levels of miR-451-5p appeared to be protective against kidney fibrosis [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 ). Furthermore, it has been shown that hsa-miR-224 expression induced in acetaminophen-induced hepatotoxicity 55 . Thus, environmental toxins-induce miR-224 expression during liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…We referred to the miRNA array data from GEO nos. GSE42181 and GSE42182 and a reference 39 to determine the Fig. 4 miR-185-5p participates in the regulation of p66Shc expression.…”
Section: Mir-185-5p Participates In the Regulation Of P66shc Expressionmentioning
confidence: 99%